PERAN PSIKOLOGI SOSIAL DALAM BIDANG HUKUM PADA KASUS PEMBUNUHAN VINA CIREBON - Dimas Elfian Nazar Nur; Fauzi Tristianto, Talitha Fairuz Marsya Nugraha, Sulistiasih (JOURNAL OF LAW AND NATION, 2024)
This study aims to determine the role of Social Psychology in the field of Law on how an individual can influence and be influenced by others, but it can also reveal the motives of the perpetrator through the psychological side and personality analysis both from the suspect's background to what trauma or mental disorders are experienced, so that he dares to commit acts that violate the law. Just like the case that has occurred in 2016 but due to being filmed, this case is again a concern because there are still some of the perpetrators who have not been arrested, namely the Vina Murder case in Cirebon. Social psychology certainly plays an important role in this case, because it can help to understand the motivations, perceptions and social interactions that underlie the actions of criminals as well as the responses of victims and society, because the involvement of social psychology can also help the legal field in seeing from the psychological side, its effectiveness in law enforcement and determining verdicts and sentences for the defendants of the murder of Vina.